A Proposal for Revisiting Ćirić and Caristi Type Theorems in Metric Spaces - Belkassem Seddoug; Soumia Chaira; Karim Chaira (International Journal of Mathematics and Mathematical Sciences)
In this paper, we revisit the renowned fixed point theorems of Ćirić and Caristi. We propose some new fixed point theorems in a metric space with partial order. To make our results effective, several examples are presented.